2023
DOI: 10.1111/ffe.14106
|View full text |Cite
|
Sign up to set email alerts
|

The low cycle fatigue property, damage mechanism, and life prediction of additively manufactured Inconel 625: Influence of temperature

Meng Liu,
Yifang Cai,
Quanyi Wang
et al.

Abstract: Symmetrical high‐temperature low‐cycle fatigue tests were performed in this study to examine the influence of temperature on the fatigue failure mechanism of the additively manufactured Inconel 625. According to the fracture analysis, cracks initiate from the crystallographic plane at room temperature. At 600°C, oxidation of carbides leads to crack initiation. The strengthening effect of γ″ precipitation prevents crack propagating within the matrix. At 750°C, the crack becomes transgranular propagating, as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Fatigue testing was performed on 15 samples at a range of maximum stresses between 100% and 160% of the yield strength of the material with the results plotted in Figure 12. These results show that the material begins to experience run-out at 100% of yield, remaining in the high cycle regime at 160% of yield; hence, it exceeds the previously published performance of wrought and welded material [28,29,47], while closely matching the results found for material produced through PM and HIP [27].…”
Section: Mechanical Property Testingsupporting
confidence: 81%
See 2 more Smart Citations
“…Fatigue testing was performed on 15 samples at a range of maximum stresses between 100% and 160% of the yield strength of the material with the results plotted in Figure 12. These results show that the material begins to experience run-out at 100% of yield, remaining in the high cycle regime at 160% of yield; hence, it exceeds the previously published performance of wrought and welded material [28,29,47], while closely matching the results found for material produced through PM and HIP [27].…”
Section: Mechanical Property Testingsupporting
confidence: 81%
“…Furthermore, the st was found to be comparable to previous studies of this combination of material an cess [25,46], while the elongation was found to be superior due to a reduced develo of the δ phase. This enhanced elongation was found to be beneficial to the fatigue p mance of the alloy, which was superior to the wrought alloy and comparable to oth methods [28,29,47].…”
Section: Mechanical Property Testingmentioning
confidence: 84%
See 1 more Smart Citation